Analysis of Learning Difficulties in Mathematics Among Fifth Grade SD Negeri Kalibatur Banyumas District in the 2024/2025 Academic Year - Khomsah Nur Laeli; Kuntoro Kuntoro (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the learning difficulties experienced by fifth grade students in Mathematics at SD Negeri Kalibatur, Banyumas District, during the 2024/2025 academic year. The research employed a descriptive qualitative approach using a case study method. The research subjects consisted of fifth grade students and their class teacher. Data collection techniques included observation, interviews, and documentation. The results showed that students faced difficulties in understanding mathematical concepts, using formulas and symbols, and solving word problems. The causes of learning difficulties included cognitive aspects, student motivation, attitudes, and the use of conventional teaching methods. The study concludes that there is a need to improve teaching strategies to be more interactive and contextual, as well as to provide additional motivation and guidance to help students overcome their learning challenges. These findings are expected to serve as a reference for teachers and schools in improving the quality of Mathematics education in the future.